2020
DOI: 10.1039/c9cc09055j
|View full text |Cite
|
Sign up to set email alerts
|

One simple Ir/hydrosilane catalytic system for chemoselective isomerization of 2-substituted allylic ethers

Abstract: One mild and simple Ir/hydrosilane catalytic system for isomerization of 2-substituted allylic ethers with high specificity and chemoselectivity was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…89 The pattern of 91 Zr hyperfine constants (Table 4; one large and two small) are typical for 4d z 2 1 ground states with z aligned along g1, 93 which also suggests an electronic structure tending to pseudo-trigonal planar environments. Cerium 4f 1 , Neodymium 4f 3 and Uranium 5f 3 The powder EPR spectra of 3-Ce at 7 K are characteristic of a rhombic Seff = 1/2 with three g-features characterised at X-band and one at Q-band (Figure 5a -c). The g1 value of 5.490 is less than the value of 6.55 expected for a pure |± 9 2 ⁄ ⟩, but is larger than the maximum g value for a pure |± 7 2 ⁄ ⟩ state, implying a mixed |± 9 2 ⁄ ⟩ ground doublet, consistent with the Msat value.…”
Section: Titanium and Zirconium Ndmentioning
confidence: 99%
See 2 more Smart Citations
“…89 The pattern of 91 Zr hyperfine constants (Table 4; one large and two small) are typical for 4d z 2 1 ground states with z aligned along g1, 93 which also suggests an electronic structure tending to pseudo-trigonal planar environments. Cerium 4f 1 , Neodymium 4f 3 and Uranium 5f 3 The powder EPR spectra of 3-Ce at 7 K are characteristic of a rhombic Seff = 1/2 with three g-features characterised at X-band and one at Q-band (Figure 5a -c). The g1 value of 5.490 is less than the value of 6.55 expected for a pure |± 9 2 ⁄ ⟩, but is larger than the maximum g value for a pure |± 7 2 ⁄ ⟩ state, implying a mixed |± 9 2 ⁄ ⟩ ground doublet, consistent with the Msat value.…”
Section: Titanium and Zirconium Ndmentioning
confidence: 99%
“…Transition metal (TM) silicon chemistry is well-established, with technological applications being actively developed 1 for solid-state silicide materials used in microelectronics, ceramics and catalysis, 2 and molecular silanide complexes that effect (hydro)silylation of unsaturated substrates. [3][4][5] In comparison, f-block silicon chemistry is less It has recently been demonstrated that the extent of covalency in f-block M-Si bonds can be established by a combination of 29 Si NMR spectroscopy and density functional theory (DFT) calculations. 32 However, this approach is currently limited to diamagnetic complexes and the vast majority of f-block complexes are paramagnetic; conversely, pulsed EPR spectroscopy has been applied to quantify An-C bond covalency in 5f 3 U(III) and 6d 1 Th(III) substituted Cp complexes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of 2-substituted allylic ethers under the same conditions mainly generated alkene isomerization products. 28,33 Scheme 20 Hydrosilylation of 1,1-disubstituted alkenes catalyzed by [(COD)IrCl] 2…”
Section: Scheme 18 Hydrosilylation Of Sulfur-containing Olefins With mentioning
confidence: 99%
“…To avoid these byproducts and install an additional handle to control catalyst reactivity, we sought to utilize the direct formation of (silyl)­Ni–H species through oxidative addition of Ni(0) to the Si–H bond of silanes for alkene isomerization (Figure c). A similar strategy has been used for precious metal-catalyzed alkene isomerization, and silanes (primarily PhSiH 3 ) have been used with Co as H-atom sources also for isomerization via 1-electron pathways. , Promising precedent for Ni(0) oxidative addition to silanes is shown in examples from Hillhouse, Radius, , and Peters, which show the stoichiometric formation of (silyl)­Ni–H species through direct oxidative addition of Ni(0) to Si–H bonds of molecular 2° and 3° silanes. Furthermore, Ni-based catalytic systems for hydrosilylation are known, with a key mechanistic step being oxidative addition of the Ni complex to the Si–H bond of the silane reagent prior to reactivity with alkenyl, alkynyl, or allenyl substrates. , …”
Section: Introductionmentioning
confidence: 99%